The Social Meanings of Artifacts: Face Masks in the COVID-19 Pandemic - Franziska Schönweitz; Johanna Eichinger; Johanna Eichinger; Janneke M. L. Kuiper; Fernandos Ongolly; Wanda Spahl; Barbara Prainsack; Bettina M. Zimmermann; Bettina M. Zimmermann (Frontiers Media S.A., 2022)
Since the beginning of the COVID-19 pandemic, research has explored various aspects of face mask use. While most of the research explores their effectiveness to prevent the spread of the virus, a growing body of literature has found that using face masks also has social meaning. But what social meaning does it have, and how does this meaning express itself in people's practice? Based on 413 qualitative interviews with residents in five European countries (Austria, Belgium, Germany, Ireland, and Switzerland), we found that the meanings of face masks have changed drastically during the first months of the pandemic. While in spring 2020 people wearing them had to fear stigmatization, in autumn of 2020 not wearing masks was more likely to be stigmatized. Throughout the first year of the pandemic, we found that mask wearing had multiple and partly seemingly contradictory meanings for people. They were perceived as obstacles for non-verbal communication, but also a way to affirm friendships and maintain social contacts. They also signaled specific moral or political stances on the side of face mask wearers and non-wearers alike, expressed their belonging to certain communities, or articulated concern. In sum, our findings show how face masks serve as scripts for people to navigate their lives during the COVID-19 pandemic. We conclude that public and political discussions concerning face masks should include not only evidence on the epidemiological and infectiological effects of face masks, but also on their social meanings and their social effects.